Hamiltonian Berge cycles in random hypergraphs. (8th March 2021) - Bal, Deepak; Berkowitz, Ross; Devlin, Pat; Schacht, Mathias
Abstract: In this note we study the emergence of Hamiltonian Berge cycles in random r -uniform hypergraphs. For $r≥ 3$ we prove an optimal stopping time result that if edges are sequentially added to an initially empty r -graph, then as soon as the minimum degree is at least 2, the hypergraph with high probability has such a cycle. In particular, this determines the threshold probability for Berge Hamiltonicity of the Erdős–Rényi random r -graph, and we also show that the 2 -out random r -graph with high probability has such a cycle. We obtain similar results for weak Berge cycles as well, thus resolving a conjecture of Poole.